Specific features of the free verse in Algeria in the 20th century - Rybalkin, S V (Journal of Oriental Studies, 2016)
The study is devoted to the Algerian free verse – a literary phenomenon, which became widespread in the second half of the 20th century. The new poetical form is another stage on the way of evolution of the Arabic-language Algerian poetry, which enables the authors to free from the canons of the traditional qasida. Artistic and poetical specifics of the Algerian free verse are the issue of this research. On the basis of literary analysis of the authentic texts in author’s translation the metaphors, imagery system and common lexis reviewed. Finally, the article studies the evolution of free verse in its dynamics – from the moment of its appearance till the beginning of the 21st century.